Changes in intraocular pressure after ND-yag laser posterior capsulotomy - Hassan, Hashim Thiab (International Journal of Clinical and Experimental Ophthalmology, 2020)
Background: The posterior capsule opacification (PCO) is also known as after cataract is a common complication after planned extra capsular cataract extraction (ECCE) with or without intraocular lens (IOL) implantation. The aim of this study was to evaluate the changes in intraocular pressure (IOP) after Nd-Yag laser posterior capsulotomy (LPC) for PCO. The Nd-Yag LPC is a safe and non- invasive procedure and can be performed as an outpatient procedure. Patients & methods: A total of one hundred eyes with symptomatic intact posterior capsule opacification (PCO) at Glaucoma Department of Alyarmouk Teaching Hospital fulfilling the inclusion criteria were enrolled in the study over a period of 6 months, 64 eyes were aphakic and 36 eyes were pseudophakic, the fellow eye was used as control. The base line pre-laser IOP was measured with the help of Goldmann Applanation Tonometer (GAT) and slit lamp examination before procedure. The pupils were dilated by using 1% tropicamide eye drops. Proparacaine eye drops were used 1-2 times for topical anesthesia, using Nd: YAG laser (VISULAS YAG III Carl Zeiss Meditec AG Germany), an opening of 3-4 mm was made in the posterior lens capsule, ensuring use of least possible energy. IOP was again assessed 1 hours, 24 hour and one week after the procedure. Results: IOP was checked before laser, at one hour, 24 hour and one week after laser. There was statistically significant (p < 0.001) rise in IOP at one hour in both aphakic and pseudophakic groups from a mean of 12.54 mmHg before laser to a mean of 20.79 mmHg at one hour with an average of 8.35 mmHg from baseline measurement. IOP at one hour rises from 2-5 mmHg in 30 eyes (30%), > 5 mmHg in 46 eyes (46%) and > 10 mmHg in 24 eyes (24%). Every patient had an IOP at one hour equal to or greater than 22 mmHg received anti-glaucoma drugs to control the rise in IOP. At 24 hours IOP decreased to a mean of 13.24 mmHg in both groups. No distinction was made between the aphakic and the pseudophakic groups with regard to IOP changes. In all treated eyes, best corrected visual acuity (VA) was recorded before and at one week after Nd-Yag laser application by Snellen’s chart. After performing a central capsulotomy VA increased in all patients. In no eye was the post-laser VA lower than before laser treatment. Conclusion: Photo-disruption with Nd-Yag laser is a safe and an effective method in management of PCO. However, there are several complications known to follow capsulotomy as significant rise in IOP and only if we can minimize their frequency or, better still, avoid them altogether, can we accept Nd-Yag LPC as a safe procedure in our effort to restore vision in cases of PCO.